Treatment with 24 hour istaroxime infusion in patients hospitalised for acute heart failure: a randomised, placebo‐controlled trial. (23rd January 2020) - Carubelli, Valentina; Zhang, Yuhui; Metra, Marco; Lombardi, Carlo; Felker, G. Michael; Filippatos, Gerasimos; O'Connor, Christopher M.; Teerlink, John R.; Simmons, Phillip; Segal, Robert; Malfatto, Gabriella; La Rovere, Maria Teresa; et al.
Abstract: Aim: Istaroxime is a first‐in‐class agent which acts through inhibition of the sarcolemmal Na + /K + pump and activation of the SERCA2a pump. This study assessed the effects of a 24 h infusion of istaroxime in patients hospitalised for acute heart failure (AHF). Methods and results: We included patients hospitalised for AHF with left ventricular ejection fraction ≤40% and E/e' > 10. Patients were randomised to a 24 h intravenous infusion of placebo or istaroxime at doses of 0.5 μg/kg/min (cohort 1: placebo n  = 19; istaroxime n  = 41) or 1.0 μg/kg/min (cohort 2: placebo n  = 20, istaroxime n  = 40). The primary endpoint of change in E/e' ratio from baseline to 24 h decreased with istaroxime vs. placebo (cohort 1: −4.55 ± 4.75 istaroxime 0.5 μg/kg/min vs. −1.55 ± 4.11 placebo, P  = 0.029; cohort 2: −3.16 ± 2.59 istaroxime 1.0 μg/kg/min vs. −1.08 ± 2.72 placebo, P  = 0.009). Both istaroxime doses significantly increased stroke volume index and decreased heart rate. Systolic blood pressure increased with istaroxime, achieving significance with the high dose. Self‐reported dyspnoea and N‐terminal pro‐brain natriuretic peptide improved in all groups without significant differences between istaroxime and placebo. No significant differences in cardiac troponin absolute values or clinically relevant arrhythmias were observed during or after istaroxime infusion. Serious cardiac adverse events (including arrhythmias and hypotension) did not differ between placebo and istaroxime groups. The most common adverse events were injection site reactions and gastrointestinal events, the latter primarily with istaroxime 1.0 μg/kg/min. Conclusions: In patients hospitalised for AHF with reduced ejection fraction, a 24 h infusion of istaroxime improved parameters of diastolic and systolic cardiac function without major cardiac adverse effects.